Energy policies in spatial systems: A spatial price equilibrium approach with heterogeneous regions and endogenous technologies - Erik Teodoor Verhoef; Peter Nijkamp (European Regional Science Association (ERSA), 1998)
This paper presents a framework for analysing spatial aspects of environmental policies in the regulation of trans-boundary externalities. A spatial price equilibrium model for two regions is constructed, where interactions between these regions can occur via trade and transport, via mutual environmental spill-overs due to the externality that arises from production, and via tax competition when the regions do not behave cooperatively. Explicit attention is also given to the additional complications arising from emissions caused by the endogenous transport flows.
Keywords: 330